THE INFLUENCE OF GADGETS ON THE DEVELOPMENT OF ELEMENTARY SCHOOL CHILDREN AND SOLUTIONS FOR PARENTS BASED ON THE THEORY OF PERENIALISM - Shelly Alvareza Zazkia; Siti Fatonah (Sunan Kalijaga International Journal on Islamic Educational Research, 2021)
Perennialism is a learning theory that maintains the purity of traditional teachings, and rejects modernization that rejects human life. Gadgets are products resulting from the modernization that is happening at this time. In fact, Gadgets were created to make it easier for humans to communicate between each other, but the fact is that technological advances are still being misused by some groups of people, so that they can have quite a fatal impact on these users. This research method is descriptive qualitative. This type of research is literature or literature research. Literature research is a type of research that collects data sources based on reference materials such as books, journals, articles and other scientific works. The results of this study indicate that gadgets are not a basic requirement for elementary school children, and intense supervision from parents is also needed on this problem. Keyword: Perennialism, Gadget, Primary School Children